The Influence of Competence and Work Creativity on Service Quality and Its Implications on Public Satisfaction at the Regional Revenue Agency of West Tanjung Jabung Regency - Mely, Mely; Zahari, M.; Akbar, Ali (Dinasti Publisher, 2026)
This study has several objectives, including identifying and describing competency, work creativity, service quality, and public satisfaction at the Regional Revenue Agency in West Tanjung Jabung Regency. It also aims to identify and analyze the influence of competency and work creativity on public satisfaction, both directly and indirectly through service quality. This research was conducted at the Regional Revenue Agency of West Tanjung Jabung Regency. The population was 120,740 taxpayers who received services. The sample size used Slovin's theory with a 10% margin of error, resulting in a sample size of 100. This study employed a quantitative approach with a survey method and Partial Least Square (PLS) data analysis. This study concludes that competency, work creativity, service quality, and public satisfaction at the West Tanjung Jabung Regency Regional Revenue Agency are in good and high condition. Furthermore, competency and work creativity have a positive and significant influence on public satisfaction, both directly and indirectly through the quality of employee service at the West Tanjung Jabung Regency Regional Revenue Agency.